The Place Name Gördchoy (‘Red Mount’) in the Folklore Topography of the Vishera River Basin - Anatoly V. Panyukov (Вопросы ономастики, 2022)
Seeing folklore topography as an ensemble of all topographic knowledge reflected in local folklore, the author considers the place name Gördchoy that is very revealing of the Vishera river basin folklore tradition. Genetically, the Vishera area is related to Vymskaya culture of the Permians of Vychegda. During the formation of the Vishera local ethnographic group, all its traditional infrastructures (economic, cultural, historical, religious, etc.) were focused on the upper reaches of the Vychegda basin. For a long time, there was no settled population in Upper and Middle Vychegda. In the 16th century, when first settlers came to the Upper Vychegda, the life of the Vishera people gradually refocused there. At that time, the main “entry point” to the territory of the Vishera basin was the mouth of this river and this is exactly where the toponym Gördchoy ‘Red Mountain’ was localized. Due to the emphasis on spatial and color characteristics, this toponym became a marker of the “Vishera” land border and acquired a significant folklore repertoire. Apart from that, the author considers numerous versions explaining the so-called Vishera phenomenon — the absence of rats in the Vishera basin. In this regard, he tackles both mythological plots (about the local sorcerer Tuve who cursed rats and legends about Stefan of Perm) and “anti-mythological,” scientifically grounded versions. The author shows that Gördchoy, regarded as a sacred border, also appears in local folklore as a “haunted” place. Due to the repeated overlapping of narratives that are somehow related to this object, the folklore topography of Vishera developed another layer in which Gördchoy is a local center possessed by evil spirits. After the construction of a new highway, the Gördchoy tract lost its border function for the Vishera territory and began to be perceived as a folklore image with blurred topographic coordinates.